Migraine patients exhibit abnormalities in the visual evoked potential. - Connolly, J F (1982)
An experiment is described which compared visual evoked potential (VEP) amplitudes and latencies in normal subjects and migraine patients. Several VEP abnormalities were found: at vertex and to a lesser extent at temporal sites, P100-N120 amplitudes were larger in patients; at vertex and temporal sites N120 amplitudes were larger in patients; at temporal sites patents had larger N120-P200 amplitudes but smaller P100 amplitudes. Peak latencies of the VEP were also found to be abnormal in patients. At vertex, patients had delayed N120 peak latencies while at temporal sites delays were found in the P200 latencies. Patients were subdivided according to side of headache. Right-sided headache patients showed larger temporal P100 amplitudes and larger left temporal P100-N120 amplitudes than bilateral headache patients.